The Influence of Digital Literacy, Self-Efficacy, and Social Environment on the Intention to Become an Entrepreneur among Gen-Z in Coastal Areas - Robbani, Mochammad Burhanuddin; Muzdalifah, Laily; Larassaty, Ayu Lucy; Sholikhah, Afifatus (Al-Qalam Institue, 2025)
This study aims to analyze the influence of digital literacy, self-efficacy, and the social environment on the entrepreneurial intentions of Generation Z in coastal areas. Using a quantitative approach with random sampling, this research involved Generation Z respondents from coastal regions. Data were collected through online questionnaires and analyzed using SPSS to examine the relationships between the variables. The findings indicate that digital literacy has a significant positive effect on entrepreneurial intention, suggesting that a better understanding of digital tools and business trends in the digital era opens opportunities for entrepreneurship among coastal youth. Furthermore, self-efficacy was found to significantly enhance entrepreneurial intention, with higher self-confidence fostering stronger entrepreneurial motivations. However, the social environment was found to have an insignificant negative effect on entrepreneurial intention, indicating that despite support from family, peers, and organizations, the environment does not significantly influence entrepreneurship. In conclusion, digital literacy and self-efficacy both positively impact entrepreneurial intention, while the social environment does not play a significant role in shaping these intentions.